BRANDING ANALYSIS OF CHERY MOTOR INDONESIA THROUGH THE OMODA 5 PRODUCT ON SOCIAL MEDIA INSTAGRAM @cherymotorindonesia - Rafi, Farell (Telkom University, 2025)
Negative stigma surrounding Chinese automotive products, particularly from brands within the automotive industry, is often not entirely accurate. Chery Motor Indonesia is working to change this perception through a branding strategy focused on the Omoda 5 product on social media, especially Instagram @cherymotorindonesia. The aim of this study is to understand how Chery Motor constructs its messaging on Instagram about the branding of the Omoda 5 product. The research employs a descriptive qualitative approach using data collection techniques such as observation, interviews, and documentation to explore Chery's branding strategy on Instagram @cherymotorindonesia. Effective branding involves principles of sustainability, assertiveness, visibility, and authenticity. This study analyzes Chery's branding strategy based on three main elements: Brand Positioning, Brand Identity, and Brand Personality. In terms of Brand Positioning, Chery positions itself as a global brand with high standards resulting from collaborations with Jaguar and Land Rover. Chery's products, used by over 13 million users in 80 countries, demonstrate superiority compared to other brands in Indonesia. Chery's Brand Identity is built through its products, logo, colors, and slogan, which convey an image of innovation and reliability. Meanwhile, Chery's Brand Personality is reflected in detailed Instagram content that emphasizes product innovation and quality, positively impacting both the company and the public. The study concludes that Chery Motor Indonesia has implemented an effective branding strategy to build its brand and reach its target market efficiently.